Perlindungan Hukum terhadap Pekerja Perempuan di Anantara Uluwatu Bali Resort - Ida Ayu Intan Surya Dewi; Ni Komang Arini Styawati; I Wayan Arthanaya (Jurnal Preferensi Hukum, 2022)
Development is very dependent on workers because workers/workers have a very important role as actors and the purpose of the development of legal protection, in this case, becomes essential to protect the rights of workers. The Covid-19 pandemic adds to the burden carried by female workers because of the change in the work system to work from home. Despite working, female workers are also burdened by household chores. In addition, other contributing factors that make women workers more vulnerable to layoffs are because women are considered physically and mentally weak, violence and discrimination. The purpose of this research is to describe the implementation of the regulations for women workers at the Anantara Uluwatu Bali Resort Hotel and to discuss the obstacles to the legal protection of women workers at the Anantara Uluwatu Bali Resort. The research method used is empirical legal research. Sources of legal material for empirical research usually come from interviews and observations which are the main sources of material, while sources of supporting materials are books and legal journals. The data collection technique was carried out through observation, accompanied by notes on the condition or behavior of the target object using documentation research techniques, and interview techniques. female workers who are pregnant until delivery, and rest periods. The rights and obligations of women workers at the Anantara Hotel Uluwatu Bali Resort are running well.